2013
DOI: 10.1080/02705060.2013.784880
|View full text |Cite
|
Sign up to set email alerts
|

Potential impacts of climate change on brook trout (Salvelinus fontinalis) populations in streams draining the Laurel Hill in Pennsylvania

Abstract: To establish a baseline for assessment of climate change effects on populations of brook trout (Salvelinus fontinalis) in southwestern Pennsylvania, we surveyed a collective of headwater streams for fish population status and the development of annual air and stream temperature profiles. The 20 streams selected, 10 located on each facing slope of an anticlinal fold on the Appalachian Plateau, Laurel Hill, historically supported self-sustaining brook trout populations. In these watersheds, anthropogenic activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Expert opinion often varies at multiple scales. For example, climate change is a global issue (Argent & Kimmel, 2013;Regier & Meisner, 1990), which could have drastic effects on the distribution and survival of brook trout in Ontario (Chu, Jones, Mandrak, Piggott, & Minns, 2008;Chu, Mandrak, & Minns, 2005 Conclusions from this study are that brook trout populations are perceived to be imperilled in parts of the province, much of which has been associated with urbanisation within the watersheds of southern Ontario.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Expert opinion often varies at multiple scales. For example, climate change is a global issue (Argent & Kimmel, 2013;Regier & Meisner, 1990), which could have drastic effects on the distribution and survival of brook trout in Ontario (Chu, Jones, Mandrak, Piggott, & Minns, 2008;Chu, Mandrak, & Minns, 2005 Conclusions from this study are that brook trout populations are perceived to be imperilled in parts of the province, much of which has been associated with urbanisation within the watersheds of southern Ontario.…”
Section: Discussionmentioning
confidence: 93%
“…Expert opinion often varies at multiple scales. For example, climate change is a global issue (Argent & Kimmel, ; Regier & Meisner, ), which could have drastic effects on the distribution and survival of brook trout in Ontario (Chu, Jones, Mandrak, Piggott, & Minns, ; Chu, Mandrak, & Minns, ). Expert opinion varied dramatically among waterbody types and FMZs, such that climate change was not considered a primary contemporary stressor to brook trout.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Each of our final models included climate and land cover variables that could be manipulated to build what-if scenarios. Due to long-term changes in water temperature and flow resulting from climate change, distributions of some salmonids, including brook trout, are expected to become even more constrained and fragmented (Haak et al 2010;Isaak et al 2010;Wenger et al 2011) until only fragile populations remain in small headwater stream thermal refuges (Flebbe et al 2006;Haak et al 2010;Argent and Kimmel 2013;Whiteley et al 2013;Trumbo et al 2014). Roberts et al (2009) found that the replacement of hemlock overstory with hardwood species in the Great Smoky Mountains National Park will have a negligible effect on long-term stream conditions, but impacts from the transition period from hemlock to hardwoods are likely to be significant.…”
Section: Conservation and Management Implicationsmentioning
confidence: 99%
“…), climate change (Meisner ; Flebbe et al. ; Argent and Kimmel ), and competition with nonnative species (King ; Flebbe ; Guffey ). The Eastern Brook Trout Joint Venture (EBTJV ) classified Brook Trout as extirpated in 41% of the subwatersheds examined, while another 51% of subwatersheds were found to have lost a significant portion of Brook Trout habitat.…”
mentioning
confidence: 99%